Lichen as bioindicator of air quality at buffer zone of Banjarbaru town - Rida Yuliani; Witiyasti Imaningsih; Tri Wira Yuwati (Jurnal GALAM, 2021)
ABSTRACTAir pollution is one of the main issues faced by urban areas. Therefore, morphological characteristic and colony coverage of lichen growing at different scale air-polluted area could become as a bioindicator of their air quality. This research aims to determine the condition of lichen in spots located at near and far from the main road (width ± 29 meter) in urban area at Banjarbaru town. This research used descriptive method with purposive sampling technique. Sample were obtained from 2 plots those were far and near the main road, each plot represented by samples from 5 different trees (densed canopy with minimum DBH at 25 cm). Lichens were taken at 50-150 cm above ground level using 20x20 cm quadrant plastic frame. Observation variables include the number and shape of colonies, color and type of thallus, and percentage of thallus cover. We determined 13 colonies from spots far from the main road (500-600 meter from main road). Lichen dominated by green to bluish color, thallus consist of crustose and foliose, and the average percentage of thallus cover was 28.01%. While from that near the main road (14-250 meter from main road), we determined 14 colonies predominantly consisted of white crustose lichens, and the average percentage of thallus cover was 10.01%. Traffic intensity showed to have significant effect on lichens community. The main difference can be seen from morphology and colony coverage. Based on this result, lichen can be used as bioindicator of air quality, especially air pollution caused by motorized vehicles.